Studying the Social Status and Health Concerning Rural Elderly Using the Plan for Rural Empowering - Behzad Sattari (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Elderliness is a biological process that is experienced by all living creatures, among them are human beings. Elderly population in the country is increasing, and in order to face this phenomena understanding the existing status of the country>s elderly is necessary. Methods & Materials: This research has been done within the framework of the objectives of the plan to empower the rural elderly, and in order to determine the present status of health concerning the rural elderly (such as the rate of handicap prevalence and its kinds and the rate of prevalence of diseases and their different kinds among rural elderly) with the purpose of offering different preventive medical and rehabilitation services to them. Determining the social status of the elderly with different dimensions, and also determining the basic needs of rural elderly in order to provide services suitable for them is among other objectives of this research. Results: This research uses the Descriptive-Studious method of the kind of «cross survey studies». In order to gather information and data, two kinds of questionnaires have been used: « the questionnaire for evaluating the social status and the health of elderly» and «the questionnaire for elderly need measurement». This plan has been done in Koraeem District of Nir city from Ardabil Province. The district has 34 villages, 14383 population, and 49 lindividuals whose ages are above sixty years. In order to analyze the data, descriptive statistics method (frequency and percent) together with SPSS software have been used. Conclusion: The rate of the elderly in the case mentioned above was estimated 3.41%. 28.8% of the elderly have missed their spouse and 70.1% of them are married, 14.3% are unable to do their own personal affairs, 8.6% live alone, 8.4% are under the supervision of protective institutions, 8.4% are suffering from different kinds of handicap, and the highest rate of prevalence of handicap is hearing handicap with the rate of 3.7%. 50.5% of them are suffering from different kinds of diseases. Heart diseases and blood pressure with the prevalence of 25.3% is the most prevalent disease among the elderly. 20% of the elderly are in need of nutrition, wearing clothes, and home, 19%in need of medical and hygienic services, 10%in need of rehabilitation services, 41% in need of programs for leisure time, and 10% in need of social honoring and valuation.